Fundamentals of EM Design of Radar Absorbing Structures (RAS) - Singh, Hema.; Duraisingh Daniel J, Ebison; Singh Rawat, Harish; George, Reshma; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents a detailed analytical formulation, and step-by-step design procedure for the electromagnetic (EM) design of radar absorbing structures (RAS). It discusses both the equivalent circuit model and Smith chart approach with illustrations to provide a clear understanding of the steps involved in designing multilayered RAS according to the desired specifications. This book is a valuable resource for beginners, academicians, and R&D engineers working in the field of RAS design and development.
Introduction -- Design of Radar Absorbing Structure -- Equivalent Circuit Model-based RAS Design -- Smith Chart-based RAS Design.- Conclusion.
Keywords: Telecommunication; Lasers; Microwaves, RF Engineering and Optical Communications; Communications Engineering, Networks; Laser